DETERMINATION OF PROFITABILITY PERFORMANCES OF INDUSTRIAL SECTORS BY MEANS OF TOPSIS METHOD: APPLICATION OF TURKEY - Vural Cagliyan; Nuri Omurbek; Esra Aksoy; Meltem Karaatli; Zeynep Ergen Isiklar (European Scientific Journal, ESJ, 2015)
Stock exchanges are accepted the most important instruments for the regional economies. The main reason for this is that stock exchanges provide capital to spread to the base and, also, enable the resource need of the investment platforms, whose functionality is registered, to be able to be satisfied. Stock exchanges are formed due to forming supplydemand balance on a certain asset and to managing the commercial activities. In this study the profitability performance exhibited by 39 industrial sectors that are being processed in Stock Exchange Istanbul (BİST), i n Turkey, in r espect w ith t he first h alf of the year 2 014, was examined on the sectorial basis in the framework of the criteria determined, compared to the same period of the last year. Handling the Variation of Net Sale Incomes, compared to the same period of the previous year; FAVÖK (profit, before the interest, tax, depreciation) Variation; Variation of the Essential Activity Profit; Variation of Net Profit, compared to the same period of the previous year; 2004/06 Equity Profitability, Variation Value of Equity Profitability in the periods of 2013/06-and 2014//06 as the criteria used in the study, they were analyzed by the method of TOPSIS, among the methods of multi criteria decision making. As a result, it was seen that the main metal industry showed the best performance in terms of profitability